2007
DOI: 10.1016/j.cellbi.2007.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Generation and characterization of mouse parthenogenetic embryonic stem cells containing genomes from non‐growing and fully grown oocytes

Abstract: It is known that oocytes can be activated without male contribution in vitro and develop to blastocysts which are used to isolate parthenogenetic embryonic stem cells. Unfortunately, differentiation capacity of the parthenogenetic embryonic stem cells was rather lower than fertilized embryos derived ES cells, which might be the result of the absence of male genome. It had been found that some maternally expressed genes were repressed and some paternally expressed genes were expressed in the non-growing oocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…; Shao et al . ). In addition, parthenogenetic stem cells are deficient in the expression of key paternal alleles, which could be used as a model for studying the genomic imprinting (Tada et al .…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…; Shao et al . ). In addition, parthenogenetic stem cells are deficient in the expression of key paternal alleles, which could be used as a model for studying the genomic imprinting (Tada et al .…”
Section: Introductionmentioning
confidence: 97%
“…To date, PgES cells have been successfully established in many species, including mouse, rabbit, nonhuman primates, even in humans (Kaufman et al 1983;Cibelli 2002;Brevini et al 2008). It has been proved that PgES cells are similar to ES cells from fertilization (fES cells) in most aspects, including the expression of certain stem cell markers, chromatin methylation patterns, embryoid body formation, and teratoma development (Park et al 1998;Barton et al 2001;Hwang et al 2004;Shao et al 2007). In addition, parthenogenetic stem cells are deficient in the expression of key paternal alleles, which could be used as a model for studying the genomic imprinting Deng et al 2007;Horii et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Chromosome deletions and translocations have also been reported in the hPES-2 cell line, when cultivated for 120 passages [Mai et al, 2007]. Few cytogenetic data are available on mouse pESC lines, reporting a stable karyotype during culture (up to passage 120), analyzed by standard G-banding [Shao et al, 2007;Ju et al, 2008;Shan et al, 2012].…”
Section: Parthenogenetic Embryonic Stem Cellsmentioning
confidence: 99%
“…Nestin is a marker for the ectoderm and plays a role in nerve development (Zimmerman et al, 1994); this protein has also been identified in mouse pES cells generated from growing oocytes (Shao et al, 2007). BPY2-interacting protein 1 interacts with ubiquitin protein ligase E3A (Wong et al, 2002) and may be involved in male germ cell development and male fertility.…”
Section: Discussionmentioning
confidence: 99%